[review] Pre-Socratic Understanding of Justice - Donev, Dejan (Faculty of Philosophy, Skopje, 2013)
In his book Pre-Socratic Understanding of Justice, Željko Kaluđerović, through an enviable research and reflective meticulousness, was able to conduct a comprehensive interpretation of the representation and understanding of justice, and to show at the same time why, with the later conception of justice, it became the very basis of the practical experience of Western civilization with all its subsequent institutional and consciously reflected forms.
Keywords: philosophy, justice, equivalence